From Learning Loss to Resilience: Assessing Recovery in the Post-COVID Era - Brad Uhing; Michael W Amolins (The Advocate, 2025)
The COVID-19 pandemic disrupted traditional learning in schools by abruptly transitioning to distance learning, prompting ongoing evaluation of its effects. This study extends previous research by incorporating additional data collected after two cohorts of students resumed in-person learning for multiple years. Northwest Evaluation Association Measure of Academic Progress (NWEA MAP) mathematics and reading scores were collected on students from Winter 2019 to Fall 2020 during the COVID pandemic and again in Spring 2023, and compared to NWEA normative data during the same time period. Results indicated that students saw a significant drop in mathematics scores during the pandemic, but had recovered by Spring 2023, while reading scores were mostly stable during this time. The method and results underscore how the model presented can be applied to single or multiple schools to monitor growth and gap closures over a period of time after a major shift in instructional practices.
Keywords: Distance Learning; Mathematics; Reading; Learning Loss; COVID-19